A atuação do psicólogo em serviços de atenção primária à saúde: efeitos negativos do trabalho na saúde do trabalhador - Duarte, Lucas Có Barros (2016)
This dissertation aims to explore the relationship between psychologists’ professional activity and their own mental health, drawing attention to possible negative effects of the work environment. To reach this goal and cover the complexity of the phenomenon, two studies were conducted: one quantitative and another qualitative. Participants were psychologists who work in primary health care in the state of Espirito Santo, Brazil. In the first study 32 psychologists answered an online questionnaire composed of sociodemographic questions and three instruments (i.e., Job Content Questionnaire (JCQ); Self Report Questionnaire (SRQ-20); WHOQOL-bref); responses were analyzed using IBMSPSS v.20 software. For the second study, we invited a group of six psychologists who work at family health units (Brazil’s Unidade de Saúde de Família) of Vitória to discuss their views on this matter. This approach was chosen in order to establish a dialogue, producing a co-analysis of work activity, based on the theoretical perspective of the Clinic of Activity. Additionally, with three of the participants, the technique of ‘instruction to the double’ was applied. All meetings and ‘instructions to the double’ were recorded, and the contents were analyzed with discourse analysis. Analysis of the results suggest that the psychologist's work in Primary Health Care has a high psychological demand, associated with great mental exhaustion and low quality of life. In addition to that, participants’ discourses indicate an internal fragility of the collective of psychologists working in primary care. We argue that this leads to a solitary professional performance and difficulty to deal with the unpredictable demands of the environment. We conclude discussing some of the strategies we believe can contribute to overcome the challenges encountered in the psychologist's performance with the Family Health Program (PSF) teams.